Utilitarianism and liberal religious approach and Islamic corporations: distortion vs. protection of classical Islamic law - Abd Elrahman, Nehal Brain (AUC Knowledge Fountain, 2012)
Utilitarianism and liberal religious approaches constitute two important results of Muhammed Abdou's project for modernizing Islamic law. Utilitarianism religious approach has dominated the Islamic legal field since the 19th century, the era of nationalist awakenings when Al-sanhurÄ« introduced his project on modernizing Islamic law. It requires cutting and pasting the supporting opinions to any argument from different Islamic schools of law. Liberal religious approach started gaining importance lately by modern Islamic scholars as a result of the increasing modern problems that were never discussed by classical Islamic scholars. It requires the reinterpretation of the main sources of Islamic law. The comparison between both approaches is important in revealing their effect on the content and organization classical Islamic law. The case of corporations constitutes the common discussed issue by both approaches. Modern Islamic scholars disagree on the adopted approach that reveals whether Islamic law recognizes corporations as legal persons or it does not. On one hand, Zahraa provides the jurisprudential bases for SanhurÄ«'s argument on the legal personality concept in Islamic law. He contends that Islamic law recognizes legal personality. Zahraa faced the problems of the lack of any classical discussions concerning legal personality and the lack of the legal personality terminology. Therefore, he adopted the selective approach on two different levels. On the first level, Zahraa selected the Islamic schools that declare the presumed legal status of the fetus and the missing persons in which the concepts of 'ahliyyat al-wujÅ«b and dhimma are inherent. On the second level, he selected both concepts and applied them on Islamic entities. On the other hand, Kuran is the only modern scholar who adopted liberal approach in case of corporations. He contends that classical Islamic law does not recognize corporations as legal persons. Kuran reinterpreted Islam's call for community building stated in the Qur'Ä n. This call is meant to replace the pre-Islam tribal system. Kuran contends that this call implicitly prevented the formation and the development of groups that enjoy personhood since they may affect Muslims' solidarity in the Islamic East. He supported his argument when he introduced the establishment of corporations in the Christian west where the call for community building did not exist. This explains why the historical development of entities in the Islamic East does not show any incorporated form of entities a few years after the advent of Islam. This is specifically applied to the waqf. However, a millennium later, although the effect of this call diminished, other reasons contributed to the stagnation of Middle Eastern organization. The comparison between both approaches is important in revealing their effect on the content and structure of classical Islamic law. This comparison concluded in that although Zahraa perceives a distorting method to the classical Islamic writings to prove that Islamic law recognizes legal status of Islamic entities, Kuran perceives a protecting method to the classical Islamic writings to prove that Islamic law does not recognize corporations as legal persons.